Learning design of planes using context culture traditional house Bengkulah. (March 2020) - Oktarina, D; Somakim; Darmawijoyo; Araiku, J
Abstract: In this case, the research that will be carried out aims to find out the cultural context of the bengkulah traditional house. The research subjects are students of SMP Negeri 1 Tanjung Lubuk. The method used in this research is the validation study design research method, alleged learning (Hypothetical Learning Trajectory). Through an interactive process including designing (Preliminary Design), (Teaching Experiment) and (Retrospective Analysis). Data collection is done through several things including making video recordings of class events and group work, collecting student work, giving preliminary and final tests, and interviewing students. So that it can show the process of implementing learning, that the use of the cultural context of the custom house can support students understanding material Rectangles and triangles.